The model of marketing communications effectiveness: empirical evidence from Slovenian business-to-business practice - Jerman, Damjana; Završnik, Bruno (Journal of Business Economics and Management, 2012)
The paper’s purpose is to add to the body of knowledge on marketing communication effectiveness by developing and testing the model of marketing communication effectiveness in the business-to-business markets. Based on past research from the marketing communications and business-to-business marketing literature, the model is tested to examine the impact of antecedent variables on marketing communications effectiveness and organizational performance. Our analysis indicates that a central concept of marketing communication effectiveness is influenced by different variables. We also confirmed a positive impact of marketing communication effectiveness on organizational performance in case of Slovenian companies.